Mitochondrial calcium cycling in neuronal function and neurodegeneration - Walters, Grant C.; Usachev, Yuriy M. (Frontiers in cell and developmental biology, 2023)
Mitochondria are essential for proper cellular function through their critical roles in ATP synthesis, reactive oxygen species production, calcium (Ca 2+ ) buffering, and apoptotic signaling. In neurons, Ca 2+ buffering is particularly important as it helps to shape Ca 2+ signals and to regulate numerous Ca 2+ -dependent functions including neuronal excitability, synaptic transmission, gene expression, and neuronal toxicity. Over the past decade, identification of the mitochondrial Ca 2+ uniporter (MCU) and other molecular components of mitochondrial Ca 2+ transport has provided insight into the roles that mitochondrial Ca 2+ regulation plays in neuronal function in health and disease. In this review, we discuss the many roles of mitochondrial Ca 2+ uptake and release mechanisms in normal neuronal function and highlight new insights into the Ca 2+ -dependent mechanisms that drive mitochondrial dysfunction in neurologic diseases including epilepsy, Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. We also consider how targeting Ca 2+ uptake and release mechanisms could facilitate the development of novel therapeutic strategies for neurological diseases.